Sistem Informasi Pengaduan Keluhan (Studi Kasus Unit General Affair Di PT. Lontar Papyrus Pulp And Paper Industry) - Saputra, Nurdiansyah; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2022)
There are problems that has been found in submission of complaint in PT. Lontar Papyrus Pulp and Paper Industry (LPPPI)where the members of GA Unit (General Affair) in terms of managing of mess where there is only three employees that has been charged in managing of dormitory in PT.LPPPI. so when there is an employee who need to create a request the office is closed which causes the request is pending until the office is opened or the employee can speak directly to GA Officer to convey their problem but this way very often to be forgotten and it’s really hard to create a report because the minimum of officer they have. This research aims to make employee of PT. LPPPI can provide compliant anywhere and anytime and the make sure the GA Officer can solve the problem faster. The Method used is this research is Prototype. The design tool that used in this research is UML (Unified Modelling Language). Output from this research is a prototype design of system analysis and design of Complaint Management in PT. LPPPI. This system can develop by using design that has been built.